Water accounting: A case study in the Buir Lake - Khalkh River Basin - Purevsuren Munkhtur; Batnyam Tseveengerel; Bayanjargal Bumtsend (Proceedings of the Mongolian Academy of Sciences)
Arid and semi-arid regions face increasing shortage of water resources due to climate variability and competing land and water uses, yet reliable information on water availability and consumption remains limited. This study addresses the critical gap in understanding water dynamics in such environments by analyzing the Buir Lake–Khalkh River Basin in Mongolia using the Water Accounting Plus (WA+) framework. The research aims to quantify water balance components and identify how land use and land cover types influenced water availability between 2010 and 2021. Climatic datasets from WorldClim, SSEBop, and GRACE-FO were employed to estimate precipitation (P), evapotranspiration (ET), and water yield (WY). Esimates showed an average annual precipitation of 298.5 mm, with notable peaks of 386.3 mm in 2013 and minimal below 250 mm during dry years. Similarly, ET demonstrates considerable variability, averaging 274.9 mm/year; maximum value was observed in 2013 at 434.8 mm, whereas the lowest value, recorded in 2017, was 200.4 mm. The average annual water yield for the basin is quantified at 23.8 mm, with specific land cover types, such as the steppe, yielding positive values (64.1 mm), while water bodies exhibited a significant deficit of -342 mm. Furthermore, WA+ resource and evapotranspiration sheets were generated for the years 2018 and 2019. In 2018, net inflow was calculated at 8.1 km³/year, of which 4.6 km³/year was attributable to landscape evapotranspiration, resulting in 3.5 km³/year deemed exploitable. In contrast, 2019 recorded a lower inflow of 7.5 km³/year, with 5.4 km³/year lost to ET. This research elucidates the interactions among precipitation, ET, and WY, emphasizing the critical influence of land management classes on water consumption patterns. Additionally, the findings contribute to the formulation of sustainable water management strategies in arid regions and provide a methodological framework for evaluating water resources in similarly stressed basins through the integration of remote sensing and water accounting methodologies.